2012
DOI: 10.1111/scs.12001
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of patient education during hospital visit – described by school‐age children with a chronic illness and their parents

Abstract: The findings show the importance of comprehensive patient education competence required of nurses giving education to families having children with chronic illnesses. This knowledge can be applied to promote nurses' professional training and to develop patient education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 36 publications
1
30
0
4
Order By: Relevance
“…Examples of such barriers included HCPs lacking the ability to have a dialogue with parents, only providing information verbally when additional written information and/or demonstration was needed [33], or being unable to adjust their teaching to parents' needs [27]. The challenge for HCPs of assessing parents' learning needs and communication preferences was highlighted, especially as these changed over time [17].…”
Section: Barriers To Parents' Learningmentioning
confidence: 99%
See 4 more Smart Citations
“…Examples of such barriers included HCPs lacking the ability to have a dialogue with parents, only providing information verbally when additional written information and/or demonstration was needed [33], or being unable to adjust their teaching to parents' needs [27]. The challenge for HCPs of assessing parents' learning needs and communication preferences was highlighted, especially as these changed over time [17].…”
Section: Barriers To Parents' Learningmentioning
confidence: 99%
“…HCPs developing good working relationships with parents [34], combined with creating a reciprocal atmosphere where parents would feel able to ask questions and express opinions [33], facilitated the process of teaching. Povlsen et al [27:41] suggested that with ethnic minority families it was useful for HCPs to ascertain parents' understanding of their child's condition and its 'impact on the family within the context of their cultural reality'.…”
Section: Facilitators To Parents' Learningmentioning
confidence: 99%
See 3 more Smart Citations